Wycieczki inferencyjne tłumacza z wyobraźnią w tle - Tokarz, Bożena (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
In a literary work, signals that trigger reader’s inferential excursions allow the reader’s imagination to identify with and control the represented world. They constitute an important element of sense-generating mechanism. Thanks to imagination, the translator imitates the inferential mechanism of the original on various level’s of the text’s structure, activating the imagination of the reader. The translator’s imagination is bi- or multivalent in having the linguistic-semiotic, literary, and cultural quality. Although it manifests itself in language, it goes beyond the boundaries of language. Imagination is a form of consciousness which has no object of its own, and a medium connecting a specific non-imaginary knowledge with representations. It constitutes a mind faculty shaped on the basis of sensory and mental perception. It is derived from individual principles of perception and cognition data processing. It usually requires a stymulus to activate the capabilities of the imagining subject. As a mind faculty, imagination is based on the mental capability common to all people, which is the ability to create chains of associations. Translator’s respect for inferential excursions in the original text is necessary for retaining the original meaning, regardless of whether they occur on the phonetic-phonological level (as in Ionesco’s The Chairs), or on the level of image-semantic and syntactic relations (as in translation of Apollinaire’s Zone), or on the level of syntax (as in translation of Mrożek’s short stories into Slovenian), or on the level of cultural communication (as in Slovenian translation of Gombrowicz’s Trans-Atlantic).